Effect of Aerobic Exercise on Dialysis-Related Symptoms in Individuals Undergoing Maintenance Hemodialysis - Nicholas Hargrove; Nada El Tobgy; Olivia Y. Zhou; Mark A. Pinder; Brittany Plant; Nicole Askin; Laura Bieber; David Collister; Reid Whitlock; Navdeep Tangri; Clara Bohm (2021)
Hemodialysis is associated with a high symptom burden that impairs health-related quality of life and functional status. Effective symptom management is a priority for individuals receiving hemodialysis. Aerobic exercise may be an effective, nonpharmacologic treatment for specific hemodialysis-related symptoms. This systematic review investigated the effect of aerobic exercise on hemodialysis-related symptoms in adults with kidney failure undergoing maintenance hemodialysis.We searched MEDLINE, PubMed, Cochrane CENTRAL, CINAHL, PsycINFO, SPORTDiscus, EMBASE, PEDro, and Scopus databases from 1960 or inception until April 15, 2020 for randomized controlled trials investigating the effect of aerobic exercise on hemodialysis-related symptoms, identified as prespecified primary or secondary outcomes, as compared with controls in adults on maintenance hemodialysis. We identified restless legs syndrome as the primary outcome.Of 3048 studies identified, 15 randomized controlled trials met the eligibility criteria. These studies investigated the effect of aerobic exercise on restless legs syndrome (two studies), sleep disturbance (four studies), anxiety (four studies), depression (nine studies), muscle cramping (one study), and fatigue (one study). Exercise interventions were intradialytic in ten studies and outside of hemodialysis in five studies. Heterogenous interventions and outcomes and moderate to high risk of bias precluded meta-analysis for most symptoms. Aerobic exercise demonstrated improvement in symptoms of restless legs syndrome, muscle cramping, and fatigue, as compared with nonexercise controls. Meta-analysis of depressive symptoms in studies using the Beck Depression Inventory demonstrated a greater reduction in Beck Depression Inventory score with exercise as compared with control (mean difference -7.57; 95% confidence interval, -8.25 to -6.89).Our review suggests that in adults on maintenance hemodialysis, aerobic exercise improves several hemodialysis-related symptoms, including restless legs syndrome, symptoms of depression, muscle cramping, and fatigue. However, the use of validated outcome measures with demonstrated reliability and responsiveness in more diverse hemodialysis populations is required to fully characterize the effect of this intervention.PROSPERO #CRD42017056658.